Antioxidant activity and phenolic profile of various morphological parts of underutilised Baccaurea angulata fruit - Ahmed, Idris Adewale; Mikail, Maryam Abimbola; Ibrahim, Muhammad; Hazali, Norazlanshah; Abdull Rasad, Mohammad Syaiful Bahari; Abdul Ghani, Radiah; Abdul Wahab, Ridhwan; Arief Ichwan, Solachuddin Jauhari; Yahya, Mohammad Noor Adros (Elsevier, 2015)
Baccaurea angulata is an underutilised tropical fruit of Borneo Island of Malaysia. The effect of solvents was examined on yield, total phenolic (TPC), total flavonoids (TFC), total carotene content (TCC), free radical scavenging activities and lipid peroxidation inhibition activities. The results indicated that the pulp (edible portion) had the highest yield, while methanol extracts were significantly (p < 0.01) found to contain higher TPC, TFC and TCC than phosphate buffered saline (PBS) extracts for all the fruits parts. The methanol extracts also showed remarkable antiradical activity and significant lipid peroxidation inhibition activities, with their IC50 results highly comparable to that of commercial blueberry. The variations in the results among the extracts suggest different interactions, such as negative or antagonistic (interference), additive and synergistic effect interactions. The study indicated that B. angulata like other underutilised tropical fruits contained remarkable primary antioxidants. Thus, the fruit has the potential to be sources of antioxidant components.